Lethality of entomopathogenic fungi on Dysdercus peruvianus (Hemiptera: Pyrrhocoridae) - Falconi, Francesca (2010)
We assessed the pathogenicity and virulence on Dysdercus peruvianus with a strain of Acremonium and one of Scopulariopsis isolated from infected adult D. peruvianus from Mala, Cañete, south of Lima. A strain of Beauveria sp., isolated from Schistocerca piceifrons peruviana from Ayacucho, was also evaluated. Bioassays were conducted on the fourth instar nymphs of D. peruvianus, and the concentrations used were 3,7 x108, 1,9 x108, 9,4 x107 conidia / mL for Beauveria sp., Acremonium sp. and Scopulariopsis sp. respectively. At 20 days after treatment, the highest mortality rates were caused by Beauveria sp. (83,3%) and Acremonium sp. (80%). Scopulariopsis sp. caused a mortality of 23,3%. Acremonium sp. was the more aggressive strain with a lethal time (LT50) of 3,8 days.